2021
DOI: 10.1002/uog.23533
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of presence of amniotic sac without visible embryonic heartbeat in diagnosis of early embryonic demise

Abstract: What are the novel findings of this work? This is the largest study to show that the finding on ultrasound of an amniotic sac without a live embryo (amniotic sac sign) is a reliable sign of early pregnancy failure. What are the clinical implications of this work? Incorporating the amniotic sac sign into current diagnostic algorithms could reduce by more than 10% the need for follow-up scans in cases of diagnostic uncertainty in early pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
2
Order By: Relevance
“…Zu diesem Zeitpunkt liegt die SSL bei ca. 7-12 mm [9]. Mit fortschreitendem Gestationsalter fällt die Abortrate ab [10].…”
Section: Intakte Frühgraviditätunclassified
See 1 more Smart Citation
“…Zu diesem Zeitpunkt liegt die SSL bei ca. 7-12 mm [9]. Mit fortschreitendem Gestationsalter fällt die Abortrate ab [10].…”
Section: Intakte Frühgraviditätunclassified
“…Wie im vorangegangenen Abschnitt beschrieben, sollte bei intakter Gravidität zu den entsprechenden Zeitpunkten ein Gestationssack, ein Dottersack und eine Embryonalstruktur mit Herzaktion darstellbar sein [4,5,6,7,8,9]. Auf die entsprechenden sonografischen und klinischen Befunde der verschiedenen Formen der gestörten Frühgravidität wird zugunsten der Übersichtlichkeit im jeweiligen Abschnitt des Artikels eingegangen.…”
Section: Sonografisch Und Klinischunclassified
“…Transvaginal ultrasonography is essential in the assessment of pregnancy of un known location, which can be due to early pregnancy, miscarriage, or ectopic pregnancy It is important to avoid making a false-positive diagnosis of miscarriage by using trans vaginal sonography, careful measurement of mean sac diameter and crown rump length and using safe cut-off values of these measurements in defining miscarriage [19]. A recen study showed that amniotic sac sign (the presence of amniotic sac without a live embryo is a reliable marker of miscarriage [20]. While the presence of an extrauterine gestationa sac with yolk sac and/or embryo with or without cardiac activity is indicative of ectopi pregnancy, the presence of an inhomogeneous adnexal mass ('blob' sign) or extrauterin sac-like structure ('bagel' sign) is very suggestive of a tubal ectopic pregnancy [21].…”
Section: Early Pregnancy Scanmentioning
confidence: 99%
“…Failed tubal sterilization and intrauterine devices can also increase the risk of an ectopic pregnancy ( Li et al , 2015 ). More recent reports from the UK showed a prevalence of 0.05% (1:2000) in women attending early pregnancy units (EPUs) ( Dooley et al , 2021 ) and 0.04% (1:2500) in ART pregnancies ( Santos-Ribeiro et al , 2016 ), probably reflecting the move towards single embryo transfers.…”
Section: Introductionmentioning
confidence: 99%